The Influence Of Brand Awareness On Purchasing Decisions Of 212 Sharia Cooperative Members - Isra Hayati; Wira Handika (UIN Mataram, 2021)
This study aims to determine how the influence of brand awareness on purchasing decisions of members of the 212 Islamic cooperative. The approach used in this research is a quantitative approach. The data analysis techniques used in this study were validity and reliability tests, classical assumption tests, multiple linear regression analysis, t test and F test and the coefficient of determination. The results showed that Brand Awareness had a positive effect on purchasing decisions of 212 sharia cooperative members obtained from the value of tcount> ttable (6.979> 1.99006), with a significance (0.000 <0.05). Thus more and more people understand Brand awareness more and more people are making purchasing decisions at the 212 sharia cooperative.